2022
DOI: 10.33545/26633582.2022.v4.i1a.68
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer detection based on thermographic images using machine learning and deep learning algorithms

Abstract: According to the latest data, breast carcinoma is the most prevalent kind of cancer in the world, and it is responsible for the deaths of almost 900 thousand people each year. If the disease is detected at the early stage and diagnosed properly, it can improve the chance of positive outcomes, thus reducing the fatality rate. An early diagnosis in fact can help in preventing it to spread and saves the premature victims from obtaining it. When trying to distinguish among benign and malignant tumors, as well as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…The breast cancer dataset from Wisconsin is utilized for comparison. (Allugunti 2022) Based on the assessment findings, the random forest approach yielded the highest accuracy (99.76%) with the lowest amount of error. Every experiment may be carried out repeatedly thanks to the use of the Anaconda Data Science Platforms.…”
Section: Et Al (2020) Containmentioning
confidence: 97%
“…The breast cancer dataset from Wisconsin is utilized for comparison. (Allugunti 2022) Based on the assessment findings, the random forest approach yielded the highest accuracy (99.76%) with the lowest amount of error. Every experiment may be carried out repeatedly thanks to the use of the Anaconda Data Science Platforms.…”
Section: Et Al (2020) Containmentioning
confidence: 97%
“…Allugunti [ 19 ] suggested a computer-aided diagnosis (CAD) approach for classifying patients into three categories (non-cancerous, no cancer, and cancer) and making a diagnosis using a database. The author studied and examined three efficient classifiers for the classification stage: CNN, SVM, and random forest (RF).…”
Section: Literature Studymentioning
confidence: 99%
“…The results of the evaluations showed that the random forest algorithm achieved the highest level of accuracy (99.76%) with the least amount of error. The Anaconda Data Science Platforms were used to run all the experiments in a reproducible environment [26]. The authors (Allugunti 2022) proposed an approach for breast cancer that classifies the disease into its various subgroups.…”
Section: Literature Reviewmentioning
confidence: 99%